2018
DOI: 10.1155/2018/6237592
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Heat Irreversibility in a Thin Film Flow of Couple Stress Fluid on a Moving Belt

Abstract: This article addresses the inherent heat irreversibility in the flow of a couple stress thin film along a moving vertical belt subjected to free and adiabatic surface. Mathematical analysis for the fluid-governing-equations is performed in detail. For maximum thermal performance and efficiency, the present analysis follows the second law of thermodynamics approach for the evaluation of entropy generation rate in the moving film. With this thermodynamic process, the interconnectivity between variables responsib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…It has found applications in several areas like biomedical [34], synovial joints (shoulder, hip, knee and ankle) fluid [35], animal blood [36], slider bearing [37] and lubricants with tiny polymer additives [38]. Furthermore, several investigations have been conducted to attest to the significance of couple stress fluid [39][40][41][42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…It has found applications in several areas like biomedical [34], synovial joints (shoulder, hip, knee and ankle) fluid [35], animal blood [36], slider bearing [37] and lubricants with tiny polymer additives [38]. Furthermore, several investigations have been conducted to attest to the significance of couple stress fluid [39][40][41][42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies were also reported for the thin film flow with various aspects. [6][7][8][9] In the recent investigations of thin film flows, Dandapat et al 10 explored the double-layer thin film flow over a stretching sheet. The asymptotic method was employed to solve the similar differential equations.…”
Section: Introductionmentioning
confidence: 99%